The Identification of Misconceptions in The Material Origin Of Life in Terms of Student Learning Outcomes - Khairuna Khairuna; Alya Nur Abdila (Jurnal Penelitian Pendidikan IPA, 2022)
Madrasah Aliyah as an Islamic-based school is assumed to be influenced by polemics between clergy and scientists about evolutionary material, especially in the theory of the origin of life. Often teachers try to relate the material about the origin of life to the study of the Qur'an and hadith, but students still experience difficulties and errors in understanding concepts. This raises the curiosity of researchers to find out how big the percentage of misconceptions experienced by students on the origin of life material and what factors influence it. This study uses a qualitative method with purposive sampling technique. Based on the identification results, it was found that in the material origin of life there were still misconceptions in the sub material of Abiogenesis theory with a percentage of 47.00%, Biogenesis theory with a percentage of 41.00%, and Cosmozoa Theory with 35.00%.Â  Some of the factors that influence it come from students, teachers and the teaching materials used